IdeaGens: A Social Ideation System for Guided Crowd Brainstorming - Chan, Joel; Dang, Steven; Kremer, Peter; Guo, Lucy; Dow, Steven (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Many crowd ideation systems seek to gather scores of ideas from people online. However, this often leads to many bad ideas and duplication. A dedicated facilitator who guides exploration of the solution space is a common and effective strategy for optimizing ideation in face-to-face brainstorming, but has not yet been explored in computer-supported crowd ideation. We introduce IdeaGens, a social ideation system for guided crowd brainstorming. IdeaGens divides the crowd into ideation and synthesis tasks, and enables efficient data-driven facilitation of the crowd’s ideation. This work can inform general strategies for shepherding the crowd to produce better results for complex collaborative tasks.